KINERJA KEUANGAN PERBANKAN DAN HARGA SAHAM: PERANAN SUKU BUNGA SEBAGAI VARIABEL MODERASI - Meliza, Meliza; Norkhasanah, Salam; Magetana, Dewi Yuniar (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.02.TAHUN.2025DO - 10.24843/EEB.2025.v14.i02.p12, 2025)
Banking performance has an impact on the volume of financial sector stock trading and the value of financial sector transactions. Banking financial performance is a reference for investors in deciding to buy or sell banking sector shares. The purpose of this study is to analyze the effect of banking financial performance as measured by the capital adequacy ratio (CAR), net profit margin (NPM) and non-performing loans (NPL) on banking companies listed on the IDX for the period 2021 to 2023. This study also analyzes the role of interest rates as a moderating variable. The analysis technique using ordinary least square (OLS) is used to test the existence of the influence of CAR, NPM, and NPL on stock prices and the role of interest rates as a moderating variable. The results of the analysis show that NPM produces a significant positive effect on stock prices with a t-statistic value of 2.55 with a significance of 5 persen. NPL has a significant negative effect on stock prices with a t-statistic value of -2.03 with a significance of 5 persen. Meanwhile, interest rates have succeeded in strengthening the influence of NPL and stock prices with a t-statistic value of -3.11.